A study on relationship between computer games usage and educational progress - Samaneh Hajikhanian; Mirsaeid Hosseini Shirvani (Management Science Letters)
This paper presents an empirical investigation on the effects of the computer games on some female students who attended the secondary schools in Iran over the period 2013-2014. The population of the survey includes 7542 female students who attend secondary schools in Babol County, Iran. The study selects 364 people as a sample and the sampling was accomplished based on random cluster way. The necessary data were collected using two questionnaires of computer games and decline of study with 25 questions in Likert 5 points and there were validated by experts and specialists in the field of educational technology and psychology. In addition, Cronbach alpha was calculated as 0.828, which was well above the minimum acceptable level. Using Pearson correlation test as well as one-way t-student, the study indicates that most female students of secondary school in Babol County used computer games. In our survey, there was a strong relationship between computer games with decline of study and study motivation, and there was a weak relationship between computer games and learning of girl students of secondary school in Babol County.